Ветер времени: роман / Дмитрий Балашов - Балашов Дмитрий Михайлович (Современник, 1990)
Экземпляры: (20240314) / Инвентарный номер: 23957 / Цена: 3.90 / Сис.шифр: Р2 / Авт.знак: Б 20 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6